Acidulants and pH regulators: unconventional ingredients for tartness and balance - Butt, Abdullah Ahmed; Kirbag, Sevda; Mahmood, Qamer (Elsevier, 2025)
In the quest to enhance sensory appeal, the utilization of acidulants and pH regulators has emerged as a fascinating avenue for culinary exploration. This chapter delves into the multifaceted world of these ingredients, elucidating their roles in achieving tartness and balance in diverse culinary creations. Beginning with an introduction to their functionality and importance, it navigates through both traditional and unconventional options, providing insights into their flavors and applications. By exploring the delicate balance of pH in flavor perception and practical tips for effective utilization, it equips readers with the knowledge to masterfully wield these ingredients. Furthermore, it delves into innovations and trends, including clean label considerations and sustainability concerns. Through a blend of theoretical understanding and practical application, this chapter offers a comprehensive guide for chefs, food scientists, and culinary enthusiasts alike. Whether concocting beverages, baking delectable treats, or crafting savory sauces, the judicious incorporation of acidulants and pH regulators promises to elevate culinary creations to new heights of taste and satisfaction. © 2026 Elsevier Inc. All rights reserved..
Keywords: Buffering agents; colloidal stability; fermentation by-products; mineral interactions; sensory modulation; titration curves